Interaksi Simbolik Agama dan Budaya dalam Tradisi Merti Desa di Dusun Ngaglik, Desa Seloprojo, Ngablak, Magelang - Mahatva Yoga Adi Pradana; Faidatun Nisak; Siti Musyafiah; Muhammad Fiqri F (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2022)
The relationship between religion, culture and society cannot be separated. All three have important positions in human life. As is commonly known, this culture is a work of humans which is then implemented or applied in everyday life. Religion itself is a belief which is then used as a guide for human life. So do not be surprised if in human life can not be separated from the name of culture and religion. For example, the Javanese people. The Javanese people are usually very thick with their beliefs. Even their belief in spirits and sacred objects is still very strong. Although the majority of the community is Muslim, besides that, their traditions and culture related to spirits, sacred objects, sacred places, and offerings are still very difficult to eliminate. Even though we as Muslims know that believing in such things is prohibited or forbidden by religion, it cannot be abandoned on the grounds that it has been passed down from generation to generation. Examples of habits that may still be preserved today are giving offerings to spirits and sacred places. For example, when Merti Hamlet will be held. When viewed from the procedure and purpose of giving offerings, namely by asking for smoothness and blessings, of course it can be said that it is not in accordance with the teachings of Islam. However, from all the Merti Hamlet events, which lasted approximately 5 days, they still carried out Islamic religious procedures. It is proven by the existence of a feast which is then filled with tahlilan, reading prayers together, and at the end of the event also holding the reading of the holy verses of the Qur'an together. So, even though there are some procedures that are not in accordance with the teachings of Islam, from the whole series of events, people still use procedures that are in accordance with the Islamic religion. In other words, people are able to acculturate the traditions of their ancestors who believe in mystical things, but they also do not forget the teachings of Islam in its implementation.